2022
DOI: 10.1177/08933189211062250
|View full text |Cite
|
Sign up to set email alerts
|

‘The Enabling Role of Internal Organizational Communication in Insider Threat Activity – Evidence From a High Security Organization’

Abstract: This paper explores the role of internal communication in one under-researched form of organizational crisis, insider threat – threat to an organization, its people or resources, from those who have legitimate access. In this case study, we examine a high security organization, drawing from in-depth interviews with management and employees concerning the organizational context and a real-life incident of insider threat. We identify the importance of three communication flows (top-down, bottom-up, and lateral) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 68 publications
(102 reference statements)
1
2
0
Order By: Relevance
“…Finally, 35% of the students surveyed from the Professional School of Civil Engineering considered it to be high, 40% considered it to be at a regular level and 25% considered it to be at a low level. These results are supported by the research of Rice & Searle (2022), because, as in the UNIFSL organizational communication is in the medium and high levels, being the inadequate use of communication tools one of the factors that cause that there is no assertive organizational communication, thus generating a dissatisfaction among the student community. The results are supported by Kapur (2020), who states that organizational communication is considered as the descriptor of what happens within organizations through internal communication to carry out the duties, improve the structure, achieve organizational goals and objectives through good organizational interaction, it is essential for individuals to communicate with each other.…”
Section: Discussionsupporting
confidence: 56%
“…Finally, 35% of the students surveyed from the Professional School of Civil Engineering considered it to be high, 40% considered it to be at a regular level and 25% considered it to be at a low level. These results are supported by the research of Rice & Searle (2022), because, as in the UNIFSL organizational communication is in the medium and high levels, being the inadequate use of communication tools one of the factors that cause that there is no assertive organizational communication, thus generating a dissatisfaction among the student community. The results are supported by Kapur (2020), who states that organizational communication is considered as the descriptor of what happens within organizations through internal communication to carry out the duties, improve the structure, achieve organizational goals and objectives through good organizational interaction, it is essential for individuals to communicate with each other.…”
Section: Discussionsupporting
confidence: 56%
“…Both women and men in the present survey indicated exposure to ‘banter cultures’, yet research has revealed that these jokes are not innocuous, instead offering an important and subtle means for perpetrators to test the boundaries of their activities, identify like-minded individuals, and desensitize others 23 . These results also echo evidence that men tend to be less aware of such talk and its negative impact 24 .…”
Section: Discussionmentioning
confidence: 73%
“…In a meta-review of institutional failures relating to ethics and risk management, Hald et al (2021) found that trust problems were key, particularly where failures had a strong ethical component. Other research has demonstrated how distrust between work groups facilitates disengagement, counterproductive norms and risky work behaviour as individuals protect their own interests (Rice and Searle, 2022; Searle and Rice, 2018). In considering the relational component at NASA, Vaughan found that shared goals but different role responsibilities, together with dual bureaucratic and political accountability, created a context of ‘cooperative adversaries’ (Vaughan, 1996: 85) between different work groups and agencies.…”
Section: Theoretical Framework: Institutional Pillars Normalisation A...mentioning
confidence: 99%